Evaluating the Cosmetic Efficacy of Topical Micrococcus luteus Q24 Probiotic Balm: A Pilot Study in Healthy Adults - Abigail L. Voss; Stephanie A. Mattison; Sonali S. Sali; John D. F. Hale; Rohit Jain (Cosmetics, 2025)
The skin microbiome is a focus for innovative skincare. This study investigated topical semi-solid balm formulations of Micrococcus luteus Q24, a live skin-native probiotic, to enhance skin quality parameters such as hydration, pores, pigmentation, wrinkles and dryness. Firstly, the compatibility and growth-promoting effects of prebiotics and functional actives on M. luteus Q24 were evaluated, identifying oil-based actives, including vitamin E and pomegranate seed oil, that significantly boosted bacterial growth compared to oatmeal, the sole effective prebiotic tested. Subsequently, a pilot cosmetic trial assessed two M. luteus Q24-enriched balms on healthy adults utilising a cutting-edge AI (Artificial Intelligence) driven skin analyser device. Balm B significantly reduced keratin levels, wrinkles, and pore size, and increased hydration, while Balm A effectively reduced spots and keratin. After 4 days of application, Balm A showed mean percentage reductions of 80% in pores, 20% in spots, 60% in wrinkles, and 100% in keratin scores, while Balm B exhibited mean percentage reductions of 100% in pores, 50% in spots, 67% in wrinkles, and 80% in keratin, with a 100% increase in hydration score. Both balms demonstrated compatibility and efficacy, highlighting the potential of M. luteus Q24 in improving skin parameters. These findings suggest that balms optimise the benefits of skin-specific probiotics for microbiome-friendly skincare. Future research with larger, placebo-controlled trials is needed to substantiate these preliminary findings.